Emotional Competence as a Positive Youth Development Construct: A Conceptual Review - Patrick S. Y. Lau; Florence K. Y. Wu (The Scientific World Journal)
The concept of emotional competence as a positive youth development construct is reviewed in this paper. Differences between emotional intelligence and emotional competence are discussed and an operational definition is adopted. Assessment methods of emotional competence with an emphasis on its quantitative nature are introduced. In the discussion of theories of emotional competence, the functionalist and developmental perspectives and the relationships with positive youth development are highlighted. Possible antecedents, especially the influence of early child-caregiver, and expected outcomes of emotional competence are examined. Practical ways to promote emotional competence among adolescents, particularly the role of parents and teachers, and the future direction of research are also discussed.